The Influence of Sex (Gender) Differences on the Student Engagement and Academic Achievement of Middle School Students in China - Zhao Yangyang; Muhammad Faizal Bin A. Ghani; Kazi Enamul Hoque (Brajamusti Publication, 2024)
This article examines the influence of gender on student engagement and academic achievement of middle school students in China. School education plays a major role in reducing gender inequality and promoting equality. This study aims to analyze the influence of gender on student engagement and academic achievement in China. It is important to have a more comprehensive understanding of the influence of gender on student performance. A quantitative survey method was used to conduct a T-test to compare the means between boys and girls in their engagement and academic achievement. Simple random sampling was used to select participants from secondary schools in China (n = 341). The findings of the study indicate that student gender does not significantly affect student engagement or have a significant impact on academic achievement. This study analyzes the findings in terms of the changing role of women in China's rapid development and changes in Chinese culture and policies, which predict important implications for advocating for gender equality in education. The practical contributions of this study are for teachers, school managers, and parents to formulate strategies to eliminate gender inequality, especially in educational institutions.